Poster 167: Biomechanics of a Novel Dermal Augmentation Procedure for Subcritical Bone Loss. Issue 7 (30th July 2022) - Wynkoop, Aaron; Wang, Patrick; Konicek, John; Akhavan, Sam
Objectives: Subcritical glenoid bone loss has been associated with high failure rates when treated with standard labral repair. While a Latarjet can provide stability, high complication rates and the risk of long term arthritis makes this procedure less then ideal when bone loss is under 20%. The purpose of the current study was to demonstrate biomechanical results of a new arthroscopic procedure using dermal allograft augmentation of subcritical bone loss when compared to a standard labral repair for subcritical bone loss. Methods: Six cadaveric specimens were prepared sequentially to simulate four clinical scenarios (Figure 1): 1) an intact shoulder; 2) a 15% bony glenoid defect; 3) 15% defect repaired using a 3-anchor labral; and 4) Dermal Allograft augmentation of the bony defect. The glenoid was potted on a ball-bearing base allowing horizontal degrees of freedom, with 50N weights applied to simulate intra-articular compression. The humerus was potted and placed in an Instron at 45 degrees of abduction, allowing anterior translation to dislocation. Translation (mm) and force (N) to dislocation were measured, using ANOVA for statistical analysis. Results: Dermal augmentation of the 15% defect resulted in a significantly higher force to dislocation (20.53+/-7.76N) when compared to the defect group (14.75+/-4.99N, p=0.002) or the labral repair (13.94+/-4.13N, p=0.007). There was no difference between the force to dislocation between the defect and labral repair groups (p=1.0). The intact shoulder translated 8.37+/-1.06mm prior to dislocation. This was significantly higher than both the defect (5.23 +/- 0.65mm, p<0.001) or the labral repair (6.55+/-0.97mm, p=0.048). The dermal augmentation resulted in no significant difference in anterior translation to dislocation (8.92 +/- 4.13mm, p=1.0). Conclusions: While labral repair is often used in patients with subcritical bone loss, clinical failure rates are high, ranging from 25-100%. Results of the current study indicate that a standard labral repair does not restore the force to dislocation when used in a 15% defect. On the contrary, it may lead to tightening of the shoulder in a non-anatomic position, resulting in the repair being "tested" at earlier range of motions. This may cause the repair to stretch during every day range of motion. Dermal augmentation of the glenoid defect can restore the normal anterior translation of the shoulder, while also increasing the force to dislocation when compared to a standard repair.